Balancing conservation and traditional use of yellow-spotted river turtle (Podocnemis unifilis) in Southern Rupununi, Guyana - van Vliet, Nathalie; Millar, Neal; Roberts, Rudolph Anthony; Braga-Pereira, Franciany (Frontiers in Ecology and Evolution, 2025)
The yellow-spotted river turtle (Podocnemis unifilis) is widely distributed across the Amazon, Orinoco, and Essequibo River basins. Studies from the Amazon and Orinoco regions highlight the species’ importance to local communities for food, income, and cultural heritage, as well as the significant threats it faces. To expand knowledge in the Essequibo River basin and assist with population management, the goal of this study was to assess turtle and egg consumption, as well as nest and turtle numbers, in the South Rupununi River in Guyana, and finally to propose sustainable management strategies that balance conservation goals with community needs, by comparing egg consumption rates with potential flood-related losses. Based on interviews conducted with 125 out of 185 Wapichan households from Sand Creek community, our findings showed that 12.0% of households (n = 15) collect annually an average of 41.87 eggs per household, while 22.4% of households (n = 28) harvest an average of 3.32 turtles per household per year. Households with more children tend to consume higher amounts of turtle eggs and meat, and those engaging in turtle harvesting report higher levels of turtle meat consumption. The primary motivation for turtle capture is consumption, particularly during culturally significant occasions, though turtles are also used for local trade, as pets, and for their shells. At the community level, the estimated annual consumption of 929 eggs is lower than the estimated 1,210 eggs lost annually to flooding on monitored beaches. However, the estimated 138 turtles harvested village-wide exceeds the number of adult turtles observed per survey day in 2021 (n = 13) and 2022 (n = 19). Our analysis suggests that during years with early floods, local egg demand could be met by rescuing at-risk nests located near the river, without increasing natural egg mortality. To offset wild turtle harvests, we recommend hatching at least 182 rescued eggs ex-situ and managing them through extensive farming systems. This approach could reduce adult turtle harvests, particularly of females. To achieve sustainable management, we propose monitoring all beaches where eggs are harvested, implementing a nest rescue program during floods, and establishing extensive turtle farming systems. These measures could shift egg harvesting from wild populations to controlled ex-situ programs, helping to conserve the yellow-spotted river turtle while supporting community needs.